Power dynamics as a determinant of access and utilization of nutrition services by pregnant and lactating adolescent girls in Trans-Mara East Sub-County, Narok County, Kenya - Charles O. Opiyo; David Omondi Okeyo; Sussy Gumo; Elly O. Munde; Zablon O. Omungo; Maureen Olyaro; Rachel K. Ndirangu; Nanlop Ogbureke; Sophie Efange; Collins Ouma (BMC, 2020)
Abstract Background During pregnancy or lactating, adequate nutrition for adolescents becomes critical to reduce risks for both child and maternal-related morbidity and mortality. Power dynamics play a massive role in health outcomes. The main objective of this study was to examine the power dynamics in the families and communities and their impact on the pregnant and lactating adolescent girls' access and utilization of nutrition services in Trans-Mara East Sub-County, Narok County. Methods A cross-sectional approach that employed mixed methods with both quantitative and qualitative research was adopted. Probability proportionate to size sampling techniques using cluster and simple random methods were used to practically access pregnant or lactating adolescents. Data was collected using questionnaires, in-depth interview and Focus Group Discussion. Quantitative data was analyzed descriptively using frequencies and inferentially using odds ratio and Z-test. Framework analysis was employed to analyze qualitative data. P ≤ 0.05 was considered statistically significant. Results In the power dynamics analyses, the intrinsic capability (Intrinsic capabilities are those adolescent driven initiatives that facilitate their access to nutrition services) was more likely to decrease awareness by half (OR = 0.52, 95% CI = 0.4-0.7, P < 0.01) whereas extrinsic dependency was likely to increase utilization by 1.2 times (OR = 1.2, 95% CI = 1.0-1.5, P = 0.055). From the stakeholder power matrix, the health personnel had observable visible power to influence access and utilization of nutrition services. Additional results revealed that adolescents who draw their support from significant others were more likely to utilize nutrition services as compared to those who attempted to make their own efforts to seek these services. Furthermore, health personnel have the most influential powers in ensuring adolescents access services and thus the most important actors in the stakeholder matrix. Other actors requiring focus included parents, political figures and governments while stakeholder engagement have higher potential of increasing access and utilization of services through dialogue. Conclusions Community access to nutritional services can be increased through use of multiple avenues to reach adolescents, including school-based, health system-based, community-based approaches and even marriage registries. A heightened engagement in the identified stakeholder network is necessary when planning community conversations, to ensure a multi-stakeholder approaches in meeting the nutrition needs of adolescents.